Mengembangkan Kreativitas Dan Berpikir Kritis Melalui Keterampilan Menulis Di Sekolah Dasar - Juleha Nirmayansha (Prodi PGSD Unsultra, 2023)
Writing skills play an important role in developing creativity and critical thinking skills of elementary school students. This paper aims to analyze various literatures on the relationship between writing, creativity, and critical thinking in the context of elementary education. Using a literature study approach, this study identifies effective learning strategies and methods to improve writing skills as a means of developing student potential. The results of the study indicate that an approach based on exploring ideas, using technology, and collaborative learning can encourage students to think critically and creatively through writing activities. The implications of this study provide a basis for designing more effective writing learning programs in elementary schools.